Contradictory Reforms: When NCLB Undermines Charter School Innovation - Peter Clyde Martin (Arizona State University, 2015)
The article discusses how instead of being parts of a concerted educational reform effort, No Child Left Behind (NCLB) and the development of charter schools are in fact contradictory initiatives.  Basing itself on a theoretical framework that brings together issues inherent to outcome-based school reform and arguments supporting and criticizing both NCLB and charter schools, the article examines the case of a specific charter school whose program was significantly altered due to pressures imposed by NCLB.  School reports, plans, programmatic descriptions, and other documents are reviewed to examine how the school responded over a three-year period to low test scores that may or may not have been a reflection of instructional quality and how NCLB requirements eventually led it to move far away from its original reform-minded mission.  Implications regarding how NCLB can undermine the innovative possibilities of charter schools are discussed.